Faces in the Clouds : a New Theory of Religion. - Guthrie, Stewart Elliott (Oxford University Press, 2015)
Religion is universal human culture. No phenomenon is more widely shared or more intensely studied, yet there is no agreement on what religion is. Now, in Faces in the Clouds, anthropologist Stewart Guthrie provides a provocative definition of religion in a bold and persuasive new theory. Guthrie says religion can best be understood as systematic anthropomorphism--that is, the attribution of human characteristics to nonhuman things and events. Many writers see anthropomorphism as common or even universal in religion, but few think it is central. To Guthrie, however, it is fundamental. Religion, he writes, consists of seeing the world as humanlike. As Guthrie shows, people find a wide range of humanlike beings plausible: Gods, spirits, abominable snowmen, HAL the computer, Chiquita Banana. We find messages in random events such as earthquakes, weather, and traffic accidents. We say a fire "rages," a storm "wreaks vengeance," and waters "lie still." Guthrie says that our tendency to find human characteristics in the nonhuman world stems from a deep-seated perceptual strategy: in the face of pervasive (if mostly unconscious) uncertainty about what we see, we bet on the most meaningful interpretation we can. If we are in the woods and see a dark shape that might be a bear or a boulder, for example, it is good policy to think it is a bear. If we are mistaken, we lose little, and if we are right, we gain much. So, Guthrie writes, in scanning the world we always look for what most concerns us--livings things, and especially, human ones. Even animals watch for human attributes, as when birds avoid scarecrows. In short, we all follow the principle--better safe than sorry. Marshalling a wealth of evidence from anthropology, cognitive science, philosophy, theology, advertising, literature, art, and animal behavior, Guthrie offers a fascinating array of.